Nutrient use efficiency and harvest index of cassava decline as fertigation solution concentration increases - Omondi, J.O.; Lazarovitch, N.; Rachmilevitch, S.; Boahen, S.; Ntawuruhunga, Pheneas; Sokolowski, E.; Yermiyahu, U. (Wiley, 2018)
Response of cassava (Manihot esculenta Crantz) to fertigation as a form of nutrient delivery is unknown. The objectives of this study were to establish a balanced nutrition and to enhance agronomic nutrient use efficiency (ANUE) of cassava under fertigation. This study was conducted in the greenhouse and in the field. In both, the results showed a similar trend. There were six fertigation concentrations and three cassava varieties, selected for their duration of growth in the field. Shoot biomass of the long‐duration variety (Nalumino) was the highest, even though its dry root yield was the lowest (10.18 t ha−1) among the varieties. In contrast, the medium‐duration variety (Kampolombo) produced the highest dry root yield (20.34 t ha−1) and a lower shoot biomass. The highest root yield of the shortest‐duration variety (Mweru) was achieved at 200 mg N, 30 mg P, and 200 mg K L−1 (155.0, 23.3, 155.0 kg N, P, K ha−1), while Nalumino's was at 70 mg N, 7 mg P, and 70 mg K L−1 (54.3, 5.4, 54.3 kg N, P, K ha−1). ANUE and harvest index of these varieties declined as the fertigation concentrations increased. Additionally, the correlation between concentrations of N in the youngest fully expanded leaf (YFEL) blades and dry root yields was the lowest (R2 = 0.5488), whereas P and K were R2 = 0.7237 and R2 = 0.8006, respectively, an indication that nutrient concentrations in the leaf, especially N, cannot easily be used to predict root yield. When cassava reaches nutrient sufficiency, mainly N, its accumulation in the leaf continues without significant increase in the root yield.